(untitled) (Publicaciones en Ciencias y Tecnología, 2019)
This paper addresses the problem of forming work teams in the most diverse way possible, given that it is demonstrated that work teams that are diverse, functionally and demographically, are more efficient in solving problems. For this purpose, we adapted an optimization model to a maximum diversity problem, with the creation of an algorithm based on GRASP metaheuristics this was efficient. In the investigation, a solution algorithm is proposed for this case of combinatorial optimization problem, it is type of strongly np-hard, the algorithm was used specifically for the conformation of survey teams, they collect data for different surveys prepared by the National Institute of Statistics and Census of Ecuador.